Comparative study of long-term displacement measurement methods − Focusing on a Pre-stressed concrete bridge under construction. (30th September 2022) - Lee, Junhwa; Jeong, Seunghoo; Kim, Hyunjun; Lee, Kyoung Chan; Sim, Sung-Han
Highlights: Computer vision, LiDAR, strain-based method, LVDT, and ring gauge are compared regarding their long-term application in full-scale bridge. Critical issues in long-term displacement measurement using each method are discussed through their long-term application to a pre-stressed concrete bridge under construction for 548 days. Thermo-mechanical behavior of the railway bridge in the construction stage is investigated. Abstract: Bridges continuously deflect over their entire lifetime, mostly due to fatigue, deterioration, time-varying material properties, or changes in boundary conditions. Long-term displacement can be employed in both the construction and operation stages for quality control and prognostic maintenance measures. Despite their versatile advantages, conventional sensors are limitedly employed for long-term displacement measurements owing to practical limitations such as clearance occupation, financial feasibility, long-term drift error, or insufficient displacement resolution. This study aims to demonstrate the long-term application of displacement measurement methods on a full-scale railway bridge using a dual-camera system, a light detection and ranging (LiDAR) system, a strain gauge, a linear variable differential transformer (LVDT), and a ring gauge for long-term monitoring for 548 days. The resulting displacements are comparatively analyzed based on dead loads and weather conditions, elucidating the practical issues arising in the long-term displacement monitoring of full-scale bridge.